Acute effects of cigarette smoking in habitual smokers, a focus on endothelial function - Nasser M. Taha (The Egyptian Heart Journal, 2013)
Background: The chronic effect of cigarette (cig.) smoking is well established. The acute effect of smoking abolishes the concept, argued by heavy smokers, to decrease the number of smoked cigarettes instead of quitting. Aim: To detect the acute effects of cigarette smoking and the duration of these effects. Patients and methods: Thirty four smokers (age 21–35 years) were studied at 3 occasions; 9 h after the last cig. smoking, 5 min after one cig. smoking and 30 min after 3 cig. smoking within 30 min. They were subjected to measurement of both ventricular functions using standard and tissue Doppler imaging (TDI), aortic distensibility, stiffness and endothelial function assessment by endothelium-dependent flow-mediated dilatation (FMD) and maximum vasodilatation. Results: After one cigarette smoking, we found a statistically significant effect on blood pressure, Heart Rate, FMD percent, Dilation Ratio, aortic distensibility (P = 0.007), and aortic stiffness index (ASI) (P = 0.01). Furthermore the LV diastolic function was significantly impaired after smoking. Despite disappearance of acute effect of 3 cig. smoking within 30 min on blood pressure, Heart Rate and aortic distensibility, a significant difference was still found as regards FMD percent and dilation ratio denoting the extension of the endothelial dysfunction for more than 30 min after the last cigarette. Conclusion: Many acute changes occur following one cigarette smoking even in habitual smokers. Persistence of endothelial dysfunction parameters after smoking indicates the failure of circulation adaptation in response to such offense that might contribute to the precipitation of acute events in vulnerable patients.